2007
DOI: 10.1590/s0102-695x2007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Stem and leaf anatomy of Plectranthus neochilus Schltr., Lamiaceae

Abstract: RESUMO: "Anatomia caulinar e foliar de Plectranthus neochilus Schltr., Lamiaceae". Plectranthus neochilus Schltr. é uma erva aromática denominada boldo ou "boldo-gambá" e empregada no tratamento de insufi ciência hepática e dispepsia na medicina popular. Este trabalho investigou a anatomia caulinar e foliar, com a fi nalidade de contribuir na identifi cação dessa planta medicinal. O material botânico foi preparado de acordo com microtécnicas usuais. O caule tem secção transversal quadrangular e, em crescimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 36 publications
4
35
0
6
Order By: Relevance
“…Possui folhas pequenas, quase triangulares, dispostas compactamente, levemente amargas e de odor forte, principalmente quando está florida (Lorenzi & Matos, 2002). É usada popularmente para o tratamento de insuficiência hepática e dispepsia (Duarte & Lopes, 2007). Informações sobre produtividade vegetal, teor, rendimento e composição química do óleo essencial dessa espécie são incipientes na literatura.…”
Section: Introductionunclassified
“…Possui folhas pequenas, quase triangulares, dispostas compactamente, levemente amargas e de odor forte, principalmente quando está florida (Lorenzi & Matos, 2002). É usada popularmente para o tratamento de insuficiência hepática e dispepsia (Duarte & Lopes, 2007). Informações sobre produtividade vegetal, teor, rendimento e composição química do óleo essencial dessa espécie são incipientes na literatura.…”
Section: Introductionunclassified
“…The presence of peltate and capitate glandular trichomes is a common feature to Lamiaceae species Ascensão et al 1999), and has been reported to species from different genera (Ascensão et al 1995;Corsi & Bottega 1999;Rodrigues et al 2006;Duarte & Lopes 2007;Gonçalves et al 2010). As a rule, peltate trichomes present short stalk and a large secretory head, while in the capitate trichomes the stalk is more than half of the height of the head (Abu-Asab & Cantino 1987;Ascensão & Pais 1998;Werker 2000).…”
Section: Discussionmentioning
confidence: 95%
“…However, the studied species was not mentioned. Duarte and Lopes (2007) reported a morphological study of Plectranthus neochilus aiming at the correct differentiation between various species of the genus Plectranthus and other genus commonly called "boldo", all used in folk medicine to treat diseases of the digestive tract. The brine shrimp lethality induced by Plectranthus neochilus ethanol extract provides an indication of antitumor activity for this species, still not reported in literature, and seems to be associated with antitumor and larvicide activities for other species of the genus Plectranthus (Gurgel et al, 2009;Tadesse et al, 2009).…”
Section: Discussionmentioning
confidence: 99%